Frankenstein e a monstruosidade das intenções: a criatura como representação da condição feminina - Soares, Janile Pequeno (2015)
This research has as objective to analyze Frankenstein (1818), written by the English writer Mary Shelley (1797-1851), from a perspective of the concept of monstrosity allied to the feminist criticism, based on Gilmore (2003), Cawson (1995), Fay (1998), Gilbert & Gubar (1984), among others. Published in 1818, Frankenstein remains attractive, among other points, due to the social critic that its lines transpires when decentralizes the narrative motif out of haunted castles, family curses and ghosts that torments the characters, as the English traditional gothic novels did. Frankenstein begins a new period of the gothic novels centering the focus on the psychological limits of its characters; exploring the monstrosities from the attitudes and intentionality as a reflex of the society from the historical period that the novel is product. The fiction of Mary Shelley overflows the feminine experience originated from the contact with a society haunted for the masculine domination. Thus, our analysis is centered on the otherness of Victor Frankenstein‘s Creature as a representation for the feminine condition of its time.